Perancangan Sistem Booking Mini Soccer dengan Payment Gateway dan Dashboard Analitik Menggunakan Metode RAD - M. Iwan Setiawan; Irma Eryanti Putri; Teguh Ansyor Lorosae (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Information systems play an important role in improving the effectiveness and efficiency of sports facility rental services. S-Soccer Kota Bima still uses a conventional booking system that causes schedule conflicts, delays in confirmation, and unintegrated transaction management. This study aims to design a website-based mini soccer field booking system equipped with a payment gateway feature. The system development applies the Rapid Application Development (RAD) method through the stages of requirements planning, design workshop, and implementation. The system provides features for real-time schedule booking, customer data management, digital payments, and an administrative analytics dashboard. System testing was conducted using the Black Box Testing method on 12 testing scenarios covering registration, login, booking, payment, and data management features. The testing results indicate that all features operated according to user requirements with a success rate of 100%. The developed system is able to improve the efficiency of the booking process, accelerate payment validation, and minimize schedule conflicts compared to the conventional method previously used at S-Soccer Kota Bima.